2022
DOI: 10.1021/acs.iecr.2c02089
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Sulfur-Cured Rubbers with Enhanced Creep Resistance and Retained Mechanical Properties by Terminal Metal Coordination

Abstract: The construction of dynamic covalent polymer networks (DCPNs) is an effective way to achieve the recycling of vulcanized rubbers. However, rubbers with DCPNs were susceptible to creep, causing poor dimensional stability which limits their applications. Sulfur vulcanization is the most widely used crosslinking technology in the rubber industry owing to its excellent comprehensive performance. It is of great importance to achieve the recyclability of sulfur-cured rubbers with improved creep resistance. Herein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For example, Xu et al reported that disulfide-cured hydroxyl and pyridyl functionalized polyisoprene block copolymers exhibited excellent creep resistance in the presence of Cu 2+ ions through cationic coordination within the network. 38 Zhu and coworkers demonstrated that incorporating transition metal catalysts in polyimine vitrimers led to creep suppression due to metal-ligand coordination. 39 Physical crosslinking by hydrogen bonds has also been utilized to enhance the properties of networks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xu et al reported that disulfide-cured hydroxyl and pyridyl functionalized polyisoprene block copolymers exhibited excellent creep resistance in the presence of Cu 2+ ions through cationic coordination within the network. 38 Zhu and coworkers demonstrated that incorporating transition metal catalysts in polyimine vitrimers led to creep suppression due to metal-ligand coordination. 39 Physical crosslinking by hydrogen bonds has also been utilized to enhance the properties of networks.…”
Section: Introductionmentioning
confidence: 99%